1999
DOI: 10.1103/physrevb.60.11180
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of single-wall carbon nanotubes on liquid-metal particles

Abstract: In this paper, we propose a mechanism for the formation of single-wall carbon nanotubes ͑SWCNT's͒ focusing on the possible transition state when tube formation is initiated. The model explains the generation of SWCNT's from carbon-metal plasmas as well as by the chemical vapor deposition technique. The model qualitatively predicts the experimentally observed dependences of the diameters of SWCNT's on the experimental parameters. It also explains why very high yields of SWCNT's can be achieved with mixed metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
140
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(148 citation statements)
references
References 35 publications
7
140
0
1
Order By: Relevance
“…A detailed analysis of carbon nanotube formation mechanism using the Fe-C phase diagram was described in Ref. 35. These results are in good agreement with our recent studies, 36 where, using calorimetry measurements, we concluded the formation of iron carbide phases during carbon SWNT growth.…”
Section: M/m S = Coth͑ H/k B T͒ − K B T/ H ͑2͒supporting
confidence: 81%
“…A detailed analysis of carbon nanotube formation mechanism using the Fe-C phase diagram was described in Ref. 35. These results are in good agreement with our recent studies, 36 where, using calorimetry measurements, we concluded the formation of iron carbide phases during carbon SWNT growth.…”
Section: M/m S = Coth͑ H/k B T͒ − K B T/ H ͑2͒supporting
confidence: 81%
“…High fractions of Fe in Fe:Mo lead to formation of larger particles during the reduction step which are inactive for SWCNT growth, unless precautions are taken to avoid excessive sintering 20 (no formation of molybdate species has been reported when using CH 4 feedstock with Fe:Mo catalysts 20 and hence the chemical role of Mo in Fe:Mo is different from that in Co:Mo). The thermodynamic advantages are revealed when considering the vapor-liquid-solid model (VLS), which is the most probable mechanism for CNT growth 12,20,41 . The metallic nanoparticles are very efficient catalysts when they are in the liquid or viscous states 20 , probably because one has considerable carbon bulk-diffusion in this phase (compared to surface or sub-surface diffusion).…”
mentioning
confidence: 99%
“…Furthermore, the presence of small concentrations of Mo reduce the lower size limit of low-temperature steady-state growth from ∼0.58nmf orpureF eparticlesto ∼ 0.52nm. Our ab initio-thermodynamic modeling explains experimental results and establishes a new direction to search for better catalysts.Critical factors for the efficient growth of single walled carbon nanotubes (SWCNTs) via catalytic chemical vapor deposition (CCVD) 1,2,3 are the compositions of the interacting species (feedstock, catalyst, support 4,5,6,7,8,9,10 ), the preparation of the catalysts, and the synthesis conditions 11,12,13,14,15,16,17,18 . Efficient catalysts must have long active lifetimes (with respect to feedstock dissociation and nanotube growth), high selectivity and be less prone to contamination 19,20,21,22,23 .…”
mentioning
confidence: 99%
“…CNFs are found to have similar electronic and mechanical properties as multiwalled carbon nanotubes ͑MWCNT͒. 1,35 Today, diffusion model is widely accepted for catalytic growth of both CNFs and CNTs, 36,37 which originated from the vapor-liquidsolid mechanism for growth of whiskers ͑currently know as fibers͒ back to the 1960s. 38 As described in diffusion model, CNF/CNT deposition process usually consists of three steps: First, reactant carbon feedstock molecules ͑hydrocarbon or carbon containing compounds͒ adsorb and decompose on the surface of a catalyst; second, carbon species dissolve or diffuse into catalyst particles ͑usually in a liquid state͒; finally, carbon precipitates on opposite surface of the catalyst forming nanofiber/nanotube structures.…”
Section: Catalytic Growth Of Cnts/cnfsmentioning
confidence: 99%